FLOUTING MAXIM PRODUCED BY LAY ZHANG IN I HEART RADIO INTERVIEW : A PRAGMATICS ANALYSIS - Nastiti Ulil Azmi; Sabat, Yulianto; Sulistyaningsih (Elite : English and Literature Journal, 2024)
This research aims to find out what types of flouting maxims were dominantly committed by Ellie and Lay Zhang in the Interview also provided another insight about flouting maxims. This research used a qualitative research method and then presented in a descriptive analysis. The pragmatic analysis of the data in this research is supported by Grice's Cooperative Principle. The data of research were the utterances of the flouting maxims by Ellie as a host and Lay as an artist that gathered by observing the Interview. The flouting maxims in the interview were studied using cooperative principle by Grice's theory, namely maxim of quality, maxim of quantity, maxim of relevance, and maxim of manner. The research showed that they committed all four types of flouting maxim, with 26 utterances containing maxim violations. The researchers found seven utterances (27%) showed a flouting maxim of quantity, five utterances (19%) showed a flouting maxim of quality, eight utterances (31%) showed a flouting maxim of relevance, and six utterances (23%) showed a flouting maxim of manner. Based on the result of the data, the most dominant flouting maxim were the maxim of relevance. This interview were provides valuable insights into the dynamics of communication in the digital era.